Pharmacological evaluation of mangrove plant Rhizophora mucronata (Lam.) grown in the coastal area of Sundarbans - Most. Chand Sultana Khatun; Md. Abdul Muhit; Md. Mahmudul Hasan Maruf; Md. Asif Iqbal; S. M. Abdur Rahman (PLoS ONE, 2026)
Rhizophora mucronata , a mangrove species native to coastal region of Bangladesh, has been drawn significant interests due to its potential ecological and therapeutic values, particularly as antioxidants, antibacterial and anti-inflammatory properties. The current investigation was aimed to identify the bioactive compounds from the different fractions of Rhizophora mucronata and to determine their antioxidants, analgesic, antidiabetic, antimicrobial along with in-vitro and in-vivo anticancer properties. Total three known compounds namely N -trans-para-caffeoyl-tyramine (1) , β-sitosterol (2) and rutin (3) were isolated from the ethyl acetate fractions (ERM) and their structures were elucidated by analyzing 1 H-NMR spectral data. Dichloromethane (DRM) and ethyl acetate (ERM) fractions showed significant free radical scavenging properties (IC 50 value 12.18 and 11.7 μg/mL, respectively) compared to the standard ascorbic acid (6.36 μg/mL) in DPPH free radical scavenging assay. All three fractions exhibited notable analgesic effect in mice compared to standard drug diclofenac sodium in acetic acid induced writhing method. DRM and ERM fractions revealed significant glucose lowering effects compared to standard glibenclamide in streptozotocin induce diabetic mice model. Besides, all the fractions showed remarkable antibacterial effects (zone of inhibition 11.1–17.3 mm) against all selected Gram-positive but showed moderate activity against the Gram-negative bacteria. In-vitro cytotoxicity test of DRM and ERM fractions exhibited cytotoxic effect (IC 50 value 88.94 µg/ml and 127.6 µg/ml, respectively) against HeLa cell. The in-vivo cell growth inhibition of the three fractions on EAC (Ehrlich ascites carcinoma) cell demonstrated that ERM fraction furnished maximum cell growth inhibition (54.61%) compared to 84.83% inhibition by bleomycin. From the above findings, it is evident that ethyl acetate fractions of R. mucronata , can be exploited for future drug development and traditional medicinal applications.